Sustainability Reporting of European Healthcare Services Organizations According to GRI Standards: Management Approach - Małgorzata MACUDA; Ryszard ORLIŃSKI (Communications of International Proceedings, 2020)
In 2016, the Global Reporting Initiative transitioned from providing guidelines to setting the first global standards for sustainability reporting – the GRI Sustainability Reporting Standards, developed by the Global Sustainability Standards Board. According to the GRI Standards, general requirements for reporting the management approach cover the following disclosures: explanation of the material topic and its boundary, the management approach and its components, and evaluation of the management approach. The aim of the paper is to examine the non-financial reporting practices related to the management approach through analyzing sustainability reports prepared in line with the GRI Sustainability Reporting Standards by European healthcare services organizations. The aim was achieved by studying the GRI Sustainability Disclosure Database where non-financial reports are published, and performing a content analysis. The key findings are the following: (1) 17 organizations from only 4 European countries prepared their sustainability reports according to the GRI Standards; (2) 12 organizations communicated about all three aspects of the management approach. This research fills a research gap in the field of non-financial reporting practices related to the management approach in the European healthcare sector.
Keywords: Non-Financial Reporting; Sustainability Reports; GRI Standards; Healthcare Organizations; Management Approach.